Rezerwaty przyrody w odbiorze społecznym studium pojezierza Międzychodzko-Sierakowskiego = Public perception of the nature reserve areas study on the example of Międzychodzko-Sierakowskie lakeland - Tokarska-Osyczka, Agnieszka; Iszkuło, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The ecological awareness of the valuable area?s users should be constantly monitored. A survey regarding forms of the environment protection was developed and The Międzychodzko-Sierakowskie Lakeland inhabitants were examined.
Keywords: ochrona środowiska; rezerwat przyrody; badania społeczne; environment protection; nature reserve; sociological survey